Financing the Budget Deficit through Islami Alsukuk in Sudan and their Economic and Social Effects and the Possibility of using them in Iraq - Qaysar Rahim Jbr; Tahani Mahdi Abbas (Journal of Madenat Alelem University College, 2021)
Since the beginning of the Islamic Sukuk as a financing tool that does not take advantage of the interest of the public and the local and international sectors, it has a clear role in providing financing to the private and public sectors of different types of projects, driven by the desire of a large segment of the public to invest in the tool which is not the basis of its interest and is in conformity with the provisions of the Islamic Shariah. It is not only used to finance projects of a purely economic nature, but has been used by governments and central banks to positively influence the social reality of local communities and to bridge deficits And also in the open market operations to control excess liquidity in Islamic banks by the Central Bank, as we will note in the Sudanese experience with the Islamic Sukuk. In Iraq, there is wide scope for using this financing formula due to the obvious lack of funding directed at various types of economic projects, The continued deficit in the public budget, which requires economic decision-makers in the country to use this tool to be complementary to the two instruments of financing recognized.